The effective field theorist's approach to gravitational dynamics - Porto, Rafael A. [UNESP] (Elsevier B.V., 2016)
We review the effective field theory (EFT) approach to gravitational dynamics. We focus on extended objects in long-wavelength backgrounds and gravitational wave emission from spinning binary systems. We conclude with an introduction to EFT methods for the study of cosmological large scale structures. (C) 2016 Elsevier B.V. All rights reserved.